Legal theory and concept of law - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
In the beginning of the legal study, it is very crucial to be familiar with diverse theories and concepts of law. For that reason, this chapter briefly discusses both juristic definitions of law propounded by various jurists as well as statutory definitions of law in Malaysia; and classifications of law from various perspectives.